Cryptosporidium: Identification and Genetic Typing. Issue 1 (6th February 2017) - Šlapeta, Jan
Abstract: Cryptosporidium spp. are obligate protozoan parasites of the gastrointestinal tract of vertebrates, including humans. In the majority of human cases, the diarrheal disease cryptosporidiosis is caused by either the human‐adapted species Cryptosporidium hominis or the zoonotic Cryptosporidium parvum 'bovine genotype' (also known as Cryptosporidium pestis ). The infectious stage, environmentally resilient Cryptosporidium oocysts, are shed by the infected host. Cryptosporidium parasites are transmitted by the fecal‐oral route and are one of the major water‐borne pathogens. The cryptic nature of the microscopic Cryptosporidium oocysts coupled with the existence of several host‐adapted and zoonotic species requires molecular tools to identify Cryptosporidium spp. in either fecal or environmental samples. This unit describes methods for Cryptosporidium identification and typing using genotyping based on nuclear loci. We also provide a protocol for morphological confirmation of Cryptosporidium oocysts based on antibody labeling of the Cryptosporidium oocyst wall and a protocol for purification of oocysts from fecal material. © 2017 by John Wiley & Sons, Inc.